Pemanfaatan Ruang Akuakultur Potensial melalui Diseminasi Teknologi Budidaya Metode Vertikal untuk Meningkatkan Kapasitas Pembudidaya dan Produksi Rumput Laut di Pesisir Desa Ujung Baji Kabupaten Takalar - Nursidi Nursidi; Heriansah Heriansah; Fathuddin Fathuddin; Nur Fajriani Nursida (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Gracillaria changii is a high-value seaweed cultivated by the community on the seashore of Ujung Baji Village in Takalar Regency. This cultivation has become the local community's primary source of income, yet production and productivity are still inadequate. To address the issue, this technology dissemination aims to give cultivators with information and abilities in using the vertical method of cultivation to boost production and productivity aquaculture of G. changii . This dissemination used the Community Development (CD) method, which involved the community in every action, including planning, designing and assembling technology, implementation, and assessment. This dissemination was successful in increasing the Hati Mulia Cultivator Group's knowledge and capabilities in vertical seaweed cultivation. When compared to horizontal cultivation, this vertical cultivation technology can increase G. changii production and productivity by at least two to three times